Typhlocolitis in a horse infected with Listeria monocytogenes - Ólöf Guðrún Sigurðardóttir 1961-; Grétar Hrafn Harðarson 1953-; Sigríður Björnsdóttir 1964-; Vala Friðriksdóttir 1954- (2014)
Listeria monocytogenes (L. monocytogenes) causes clinical disease primarily in ruminants, although disease also occurs in monogastric animals, birds and humans (Clark et al. 2004, Holzer et al. 2012). The intestine is the primary port of entry for the bacterium, but the clinical manifestation of the infection is variable, including septicaemia, meningitis/meningoencephalitis and abortion (Rütten et al. 2006, Hoelzer et al. 2012). L. monocytogenes is widely distributed in the environment and has been isolated from clinically healthy monogastric mammals (Clark et al. 2004, Hoelzer et al. 2012). Large numbers of the bacteria, sometimes exceeding 106 colony forming units/g faeces, were however found in the faeces of severely ill horses in Iceland (Gudmundsdottir et al. 2004). In horses, as in other animals, L. monocytogenes causes mainly abortion, septicaemia and less frequently encephalitis (Rütten et al. 2006, Warner et al. 2012). Although a disease ascribed to alimentary listeriosis has long been recognized in horses in Iceland, little study has been done on the disease and a description of the post-mortem findings has been lacking. This paper gives an account of alimentary listeriosis in a herd of horses and describes the post-mortem findings in one of the affected individuals, a 6-month-old filly with acute typhlocolitis.